Functional deficits in post-operative adolescent idiopathic scoliosis patients - Rafferty, Anthony; Donne, Bernard; Kiely, Patrick; Fleming, Neil (My University, 2020)
BACKGROUND: Little or no research currently exists investigating musculoskeletal strength, joint flexibility and cardiopulmonary capacity post-operative adolescent idiopathic scoliosis (AIS) patients. PURPOSE: To explore if AIS patients following spinal fusion surgery have deficiencies in strength, endurance joint flexibility and pulmonary capacity (>12-month post-operative) compared to a matched sample of the general population. METHODS: This retrospective case control study; AIS group (n = 20) and control group (n = 20) matched for gender, age and anthropometrics. Participants underwent standardised tests to establish pulmonary capacity via spirometry, upper and lower limb strength via manual muscle testing, upper and lower limb endurance via press-up and wall squat tests and joint flexibility via manual goniometry. Within session reliability and reproducibility of variables were assessed. RESULTS:No significant differences between AIS and control cohorts were identified for mass (57.1±9.0 vs. 62.8±9.0kg), height (164.7±6.3 vs. 165.6±6.0cm) or BMI (21.2±4.0 vs. 22.9±2.7). Pulmonary and musculoskeletal deficiencies in the AIS cohort were identified, including significantly lower forced vital capacity (FVC; 2.6±0.5 vs. 3.3±0.5L, P < 0.001) and forced expiratory volume in 1 second (FEV1, 2.8±0.6 vs. 3.3±0.5L, P < 0.001); restrictions in shoulder flexion (P < 0.01) and internal rotation (P < 0.001) weaker bilateral pinch grip (P < 0.01) and bilateral hip adductor strength (P < 0.01). CONCLUSION: The results highlight that AIS patients still have major pulmonary and musculoskeletal impairments over a year after spinal fusion surgery. Clinicians should consider periodic assessment of pulmonary and musculoskeletal function with comparison to these age-matched reference values in order to improve the post-operative rehabilitation process.
PUBLISHED
Keywords: Scoliosis; Adolescent idiopathic scoliosis; Spinal fusion; Functional impairments; Physical activity; Muscle dysfunction; Physiology